2010
DOI: 10.1016/j.nbt.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A flexible and fully integrated system for amplification, detection and genotyping of genomic DNA targets based on microfluidic oligonucleotide arrays

Abstract: A strategy allowing for amplification, detection and genotyping of different genomic DNA targets in a single reaction container is described. The method makes use of primer-directed solution-phase amplification with integrated labeling in a closed, microfluidic oligonucleotide array. Selective array probes allow for subsequent detection and genotyping of generated amplicons by hybridization. The array contains up to 15,624 programmable features that can be designed, de novo synthesized and tested within 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Four target enrichment and three NGS methods were preliminarily evaluated for multiplexed carrier testing. Preliminary experiments suggested that existing protocols for Agilent SureSelect hybrid capture (15) and RainDance microdroplet polymerase chain reaction (PCR) (16) but not Febit HybSelect microarray-based biochip capture (30) or Olink padlock probe ligation and PCR (31) yielded consistent target enrichment. Therefore, workflows and software pipelines were developed for comprehensive carrier testing by hybrid capture or microdroplet PCR, followed by NGS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four target enrichment and three NGS methods were preliminarily evaluated for multiplexed carrier testing. Preliminary experiments suggested that existing protocols for Agilent SureSelect hybrid capture (15) and RainDance microdroplet polymerase chain reaction (PCR) (16) but not Febit HybSelect microarray-based biochip capture (30) or Olink padlock probe ligation and PCR (31) yielded consistent target enrichment. Therefore, workflows and software pipelines were developed for comprehensive carrier testing by hybrid capture or microdroplet PCR, followed by NGS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the need for highly accurate genotype detection, we developed a decision tree for identifying and genotyping mutations based on previous studies of genotypes identified in NGS genome sequen ces (Figure 5) [32,33,37,38]. SNPs in 26 samples were genotyped by both Infinium arrays and NGS.…”
Section: Sequence Analysis Strategymentioning
confidence: 99%
“…Furthermore, while traditional sample preparation, amplification, and microarray hybridization chemistries can be incorporated into a consumable via microfluidic transfer steps (9)(10)(11)(12)(13)(14)(15), the engineering, manufacturing, and quality control challenges of such consumables (and control instruments) scale with the complexity of the microfluidic architecture. An alternative approach for simplifying microarray technology for routine monitoring applications, then, is to minimize the biochemistry and processing steps that precede and interface with the microarray itself.…”
mentioning
confidence: 99%